Rechtspopulistische Rhetorik revisited am Beispiel der FPÖ-Wahlkämpfe in den Jahren 2015 und 2016 - Lehner, Sabine (Linguistik Online, 2019)
Right wing and far right parties have recently succeeded in many elections worldwide. The Austrian Freedom Party (Freiheitliche Partei Österreichs, FPÖ), one of the most successful right-wing populist parties of Europe, has lately also enjoyed great popularity in regional and national elections. Norbert Hofer, the FPÖ-candidate, even made it to the run-offs of the presidential election in 2016. This paper draws on a discourse-analytical approach and investigates the discursive strategies implemented by the FPÖ during two election campaigns (the 2015 local elections in Vienna and the 2016 presidential elections). Based on various discursive events of both campaigns (speeches, posters, TV-discussions etc.), this contribution examines if recent right-wing populist rhetoric corresponds to well-known patterns or if there have been some shifts.